Reform of The National Education System For The Sake of Optimizing The Implementation of A Curriculum System with Legal Certainty and Justice - Kimico Margaretha Tjhia; Faisal Santiago; Tina Amelia (Siber Nusantara of Law and Politic Review, 2026)
This article examines the renewal of Indonesia's national education system (2021-2025) with a focus on the rule-of-law requirements for curriculum implementation: legal clarity, accessibility, foreseeability, and enforceability. Using a doctrinal, socio, legal design, we map the hierarchy of norms governing curriculum and standards Government Regulation No. 57/2021 on National Education Standards as aligned by No. 4/2022, and the curriculum framework in Ministerial Regulation No. 12/2024 as amended by No. 13/2025, and test their coherence through the principles of lex superior, lex posterior, and lex specialis. A PRISMA-guided evidence synthesis of literature and reputable policy reports complements the legal analysis, incorporating cost-effectiveness metrics (Learning-Adjusted Years of Schooling, LAYS) to assess feasibility. Findings indicate improved legal certainty at the regulatory apex, yet gaps persist at the level of implementing provisions (definitions, transitional clauses, and operational guidance on assessment and teaching resources). The Constitutional Court's Decision No. 3/PUU-XXII/2024 elevates a positive state obligation to finance compulsory basic education without fees in both public and qualifying private schools, requiring secondary legislation to define "no-fee", eligibility criteria, prohibited charges, and remedies. To reconcile legality with equity and fiscal realism, we propose a compliance architecture comprising needs-based funding formulas, output-linked service contracts for private providers, standardised structured-pedagogy and targeted-instruction packages as cost-effective supports, and a legally based on grievance redress mechanism with sanctions and restitution. The contribution is a legally anchored, evidence-informed roadmap that balances legal certainty, distributive justice, and implementability.